A preparation method of low heat generation tire tip rubber for preventing tip from being empty and tire

By using low-thermal tire gum composed of natural rubber, styrene butadiene and polystyrene butadiene glue, and vulcanizing through the synergistic action of promoters, sulfur and zinc oxide, combined with components such as carbon black, tackifying resin and heat stabilizer, the problem of existing tire gums being prone to empty tissue gums, significantly improving the safety performance of the tire.

CN116253939BActive Publication Date: 2025-04-08ZHAOQING JUNHONG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310106343.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-12
Publication Date
2025-04-08
Estimated Expiration
2041-10-12

AI Technical Summary

Technical Problem

Existing tire glue is prone to the problem of empty sub-mouth, which leads to the tire being prone to early damage quality problems such as cracks and explosives during use, affecting the vehicle's driving safety.

Method used

A low-thermal tire mouth glue composed of natural rubber, styrene butadiene and polystyrene butadiene is used to fully vulcanize through the synergistic effect of accelerator, sulfur and zinc oxide, and combine components such as carbon black, tackifying resin and heat stabilizer to adjust the formula to improve the rigidity, tensile strength and heat resistance of the glue.

Benefits of technology

It effectively improves the rigidity, tensile strength and heat resistance of the sub-mouth glue, significantly reduces the incidence of sub-mouth hollowing, reduces the quality problems of early damage such as sub-mouth cracking and sub-mouth explosion, and improves the safety performance of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004074984450000121
    Figure BDA0004074984450000121
  • Figure BDA0004074984450000122
    Figure BDA0004074984450000122
  • Figure BDA0004074984450000131
    Figure BDA0004074984450000131
Patent Text Reader

Abstract

The present application provides a method for preparing a low-heat tire bead rubber for preventing bead hollowing and a tire, which is composed of the following components in parts by weight: 20-80 parts of natural rubber, 10-35 parts of styrene-butadiene rubber, 15-45 parts of solution-polymerized styrene-butadiene rubber, 1.0-4.0 parts of zinc oxide, 1-4 parts of stearic acid, 1-5 parts of polyethylene glycol, 1.0-3.2 parts of dispersant, 1.5-6.0 parts of antioxidant, 1.5-3.5 parts of protective wax, 3-9 parts of tackifying resin, 1-8 parts of thermal stabilizer, 45-110 parts of carbon black, 30-110 parts of silane coupling agent, 10-20 parts of styrene-butadiene rubber, 15-45 parts of styrene-butadiene rubber, 10-20 ... The invention can effectively improve the rigidity, tensile strength, tear strength, small permanent deformation, good flexure and resilience of the formula, improve the bonding force of each component, enhance the bonding strength with the surface of the contact component, have low heat generation and good heat aging resistance, and the cohesive force is greater than the destructive force generated by the outside world or high-speed movement. It can greatly reduce the empty mouth, reduce the quality problems of a series of early damages such as mouth cracking and mouth explosion, and reduce the huge threat to the safety of vehicle driving.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the original application is 2021111865202, the application date is October 12, 2021, and the name of the invention is "A tire tip rubber for preventing the tip from being empty, and its preparation method and application". Technical Field

[0002] The invention belongs to the technical field of tire manufacturing, and in particular relates to a method for preparing a low-heat-generating tire bead rubber capable of preventing bead hollowing, and a tire. Background Art

[0003] With the development of society, people's requirements for driving safety, high speed, environmental protection, etc. are gradually increasing. As the first life of automobile driving safety, tires need to be upgraded urgently. After the popularization of radial and tubeless tires, although there have been great improvements, tire accidents have been reduced by half, and tire blowouts have mostly disappeared, and it can be achieved that there are no tire problems for hundreds of thousands of kilometers. However, tire deflation and blowout are still a major concern.

[0004] Since the bead of the tire is directly connected to the rim of the car, as the tire is running, the friction between the bead and the rim causes more and more heat accumulation and higher temperature, which causes the bead rubber to produce vulcanization reverse phenomenon, thereby causing the cross-linking bonds of the bead rubber to break and the performance to decline, which in turn leads to bead empty. When the bead empty reaches a certain level, a series of early damage quality problems such as bead cracking and bead explosion will occur. The tire is prone to be bead empty due to long-term overloading during use. If the tire is bead empty and the owner fails to find it, the bead part of the tire will crack and leak when the car continues to drive, eventually leading to a tire blowout, which poses a huge threat to the driving safety of the vehicle.

[0005] Therefore, the low heat generation and heat-resistant stability of the tire bead rubber are crucial. Improving the tire bead hollow is to reduce the risk of tire bead hollow, improve the safety performance of the tire, and meet people's product needs. Summary of the invention

[0006] In order to solve the technical problem that existing tire bead rubbers are prone to bead hollows, the present invention provides a low-heat-generating tire bead rubber for preventing bead hollows, which can effectively improve the formula rigidity, tensile strength, tear strength, small permanent deformation, good flexure and resilience, and can improve the bonding force of various components and enhance the bonding strength with the surface of contacting components. It has low heat generation and good heat aging resistance, and its cohesive force is greater than the destructive force generated by the outside world or high-speed movement. It can greatly reduce bead hollows, reduce a series of early damage quality problems such as bead cracks and bead explosions, and reduce the huge threat to vehicle driving safety.

[0007] In order to solve the above technical problems, this application adopts the following technical solutions:

[0008] A low-heat tire tip rubber for preventing tip hollowing is composed of the following components in parts by weight: 20-80 parts of natural rubber, 10-35 parts of styrene-butadiene rubber, 15-45 parts of solution-polymerized styrene-butadiene rubber, 1.0-4.0 parts of zinc oxide, 1-4 parts of stearic acid, 1-5 parts of polyethylene glycol, 1.0-3.2 parts of dispersant, 1.5-6.0 parts of antioxidant, 1.5-3.5 parts of protective wax, 3-9 parts of tackifying resin, 1-8 parts of thermal stabilizer, 45-110 parts of carbon black, 3-6 parts of silane coupling agent, 2-6 parts of sulfur, 2-13 parts of accelerator and 0.1-1 part of scorch retarder.

[0009] The present application provides a low-heat tire bead rubber for preventing bead hollowing, which uses three types of rubber, natural rubber, styrene-butadiene rubber and solution-polymerized styrene-butadiene rubber, uses an accelerator, sulfur and zinc oxide to work together as a vulcanization system to fully vulcanize the rubber, uses carbon black to reinforce, uses a tackifying resin to increase the adhesion between the rubber and the skeleton material, and then cooperates with stearic acid, polyethylene glycol, a dispersant, an antioxidant, a protective wax, a silane coupling agent, a scorch inhibitor, etc. The formula is adjusted, and a heat stabilizer is innovatively added. After a large number of repeated tests, it is determined that the heat The optimal dosage of stabilizer and other components is used to obtain the above-mentioned formula. The nozzle glue formula for preventing nozzle voids of the present invention can effectively improve the formula rigidity, tensile strength, tear strength, small permanent deformation, good flexure and resilience, can improve the bonding force of various components, enhance the bonding strength with the surface of contact components, has low heat generation and good heat aging resistance, and the cohesive force is greater than the destructive force generated by the outside world or high-speed movement. It can greatly reduce nozzle voids and reduce a series of early damage quality problems such as nozzle cracks and nozzle explosions, thereby reducing the huge threat to vehicle driving safety.

[0010] Preferably, the weight ratio of the raw materials is:

[0011] 30-70 parts of natural rubber, 15-35 parts of styrene-butadiene rubber SBR1502, 15-35 parts of solution polymerized styrene-butadiene rubber SSBR2466, 1.0-3.0 parts of zinc oxide, 1-3 parts of stearic acid, 1-3 parts of polyethylene glycol, 1.5-2.5 parts of dispersant, 1.5-5.5 parts of antioxidant, 1.5-2.5 parts of protective wax, 3-8 parts of tackifying resin, 1-6 parts of heat stabilizer, 45-100 parts of carbon black, 3-5 parts of silane coupling agent, 2-6 parts of sulfur, 2-10 parts of accelerator, 0.1-0.5 parts of scorch retarder. The rubber with this ratio of components has the best performance.

[0012] Preferably, the heat stabilizer is selected from the heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd., with a melting point of ≥78.0°C (determined by GB / T11409 standard 3.1 melting point), ash content ≤28.0% (determined by GB / T11409 standard 3.7 ash content), heating loss ≤4.0% (determined by GB / T11409 standard 3.4 heating loss, 60°C / 2h), TCA-90 is a bismaleimide derivative, which can give rubber products excellent thermal stability, improve the dynamic properties of rubber products at high temperatures, reduce the heat generation of rubber vulcanized rubber, and improve the elasticity of rubber products. The use of TCA-90 and a small amount of zinc oxide to crosslink natural rubber can improve the heat resistance and adhesion of tire rubber, and make the vulcanized rubber have excellent flex fatigue and elasticity. From the perspective of tire bead rubber, this heat stabilizer is the preferred rubber to prevent bead hollows. Moreover, under high-temperature vulcanization conditions, the rubber containing TCA-90 will not experience vulcanization reversion regardless of whether NS, DPG or DTDM is used as an accelerator. The activity of TCA-90 is greatly improved in the presence of free radical reactions and accelerators, resulting in a great improvement in the heat resistance of natural rubber and the bonding strength between natural rubber and the cord.

[0013] Preferably, the natural rubber is natural rubber SMR20#, and the raw rubber in the formula of the present application is natural rubber, which has excellent tensile strength, elongation, tear strength and excellent elasticity;

[0014] The styrene-butadiene rubber is SBR1502 produced by Fujian Fuxiang Chemical Co., Ltd., which is a low-temperature emulsion styrene-butadiene rubber, with volatile matter ≤0.75%, total ash ≤0.75%, organic acid 5.62%, soap ≤0.50%, combined styrene 23.5%, tensile strength ≥23.7Mpa 35min, elongation ≥415% 35min, and good tensile strength, wear resistance and flexural properties;

[0015] The solution polymerized styrene butadiene rubber is solution polymerized styrene butadiene rubber SSBR2466, with a Mooney viscosity ML1+4 of 70-80 at 100°C and a styrene content of 20-22%. The solution polymerized styrene butadiene rubber has a high Mooney viscosity of the mixed rubber, and the end of the end-group-modified SSBR molecular chain enhances the interaction with the carbon black surface group and the coupling agent, and the molecular chain carbon black and the filler have a large interaction. After the rubber is vulcanized, the end-group-modified SSBR rubber has a functionalized group participating in the vulcanization reaction, which increases the crosslinking density, significantly improves the dynamics of the rubber, improves the wear resistance, and reduces the rolling resistance.

[0016] The present invention uses three types of rubber, namely natural rubber, styrene-butadiene rubber and solution-polymerized styrene-butadiene rubber, in combination with heat stabilizers and other raw materials, which can give rubber products excellent thermal stability, improve the dynamic properties of rubber products at high temperatures, and reduce the heat generated by rubber vulcanization;

[0017] Preferably, the carbon black is composed of three types of carbon black in the following weight ratios: 15-45 parts of N326 carbon black, 10-45 parts of N330 carbon black and 10-50 parts of white carbon black. The carbon blacks selected from Shanxi Yongdong Chemical Co., Ltd. are N326 and N330 respectively. The above three types of carbon black are used in combination. The inventors have repeatedly tested and finally determined the optimal dosage, which can ensure that the comprehensive physical properties of the rubber are good, and the performance of preventing the rubber from being empty is improved, while the hardness, tear resistance, tensile strength and tensile stress of the rubber are improved.

[0018] Preferably, the accelerator is composed of three accelerators in the following weight ratio: 0.5-3 parts of accelerator NS, 0.5-1.5 parts of accelerator DPG and 0.5-2.5 parts of accelerator DTDM. The above accelerators are easily dispersed in the rubber material. The combined use of accelerator NS, accelerator DPG and accelerator DTDM can effectively promote sulfur vulcanization. At the same time, the present application uses a heat stabilizer to avoid the occurrence of vulcanization reversion and improve product stability.

[0019] Preferably, the antioxidant is selected from at least one of N-phenyl-α-aniline, N-phenyl-N'-isopropyl-p-phenylenediamine, N-N'-diphenyl-p-phenylenediamine and antioxidant 4020, preferably antioxidant 4020, which has good solubility in the rubber material, is not easy to bloom, is not easy to volatilize, has low toxicity, has excellent resistance to oxygen, ozone, flex cracking, and sunlight cracking, and has a strong inhibitory effect on harmful metals such as copper and manganese to improve the protective effect.

[0020] Preferably, the dispersant model is KO-311. The compatible dispersant KO-311 is a liquid composite modified material, which can prevent the heat stabilizer and carbon black from precipitating during the mixing process and improve the impact resistance of the rubber.

[0021] Preferably, the tackifying resin is a styrene-maleic anhydride copolymer resin, which is a product of Cray Valley Company with a model number of SMA 3000P, a maleic anhydride content of 20-25, a weight average molecular weight of 8000-12000, and a melt viscosity of 2000-4000cps. Preferably, the styrene / maleic anhydride molar ratio in the styrene-maleic anhydride copolymer resin product is 3 / 1. The high-activity maleic anhydride group in the SMA resin as an alkali-soluble resin segment can react chemically with the functionalized group in the rubber to form a firmly bonded covalent bond, thereby improving the interfacial bonding of the rubber, thereby improving the tensile, bending, toughness and other mechanical properties of the material, and can significantly improve the heat resistance of the rubber, as well as improve the bonding force of each component, enhance the bonding strength with the surface of the contacting component, and the cohesive force is greater than the destructive force generated by the outside world or high-speed movement, which can greatly reduce the gap, reduce the gap cracking, the gap explosion and other early damage quality problems, and reduce the huge threat to the driving safety of the vehicle.

[0022] The silane coupling agent used is the coupling agent HP-669 from Jingdezhen Hongbai Chemical Technology Co., Ltd., with the chemical name bis-(3-triethoxysilylpropyl)-tetrasulfide. The cross-linking speed of the polysulfide groups of 669 is basically consistent with the sulfur reversion speed in sulfur vulcanization, which plays an anti-vulcanization reversion role, thereby improving the dynamic bending properties of rubber such as heat generation and crack extension. Poly-S atoms can also promote vulcanization.

[0023] The sulfur used is selected from granular sulfur with a sulfur content of ≥95%, preferably highly dispersed insoluble sulfur, which has the main characteristics of high thermal stability and high dispersibility.

[0024] The density of the low heat build-up tire rubber compound prepared in this application is about 1.166-1.169 kg / dm 3 ,

[0025] A second object of the present invention is to provide a method for preparing a low heat generation tire tip rubber that prevents tip emptying, comprising the following steps:

[0026] (1) Mixing: Weigh the above raw materials according to the weight ratio, transfer the weighed raw materials into the internal mixer, and mix them under a pressure of 45-55N / cm 2 , automatically mix for 180 seconds at a temperature of 145-155°C and a rotation speed of 25-45 rpm, and then discharge the glue;

[0027] (2) Extrusion tableting: After debinding, the product is extruded and tableted by a twin-screw extruder. After passing through an isolation liquid, the product is cooled and stacked.

[0028] The third purpose of the present invention is to provide a low-heat-generating tire bead rubber for preventing bead voids and its application in the preparation of bead tires. The tire bead obtained has excellent bead performance, can significantly reduce bead voids, and reduce a series of early damage quality problems such as bead cracks and bead explosions, thereby meeting customers' tire performance requirements.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] The present application provides a low-heat tire tip rubber for preventing tip hollowing, which is composed of the following components in parts by weight: 20-80 parts of natural rubber, 10-35 parts of styrene-butadiene rubber, 15-45 parts of solution-polymerized styrene-butadiene rubber, 1.0-4.0 parts of zinc oxide, 1-4 parts of stearic acid, 1-5 parts of polyethylene glycol, 1.0-3.2 parts of dispersant, 1.5-6.0 parts of antioxidant, 1.5-3.5 parts of protective wax, 3-9 parts of tackifying resin, 1-8 parts of heat stabilizer, 45-110 parts of carbon black, 3-6 parts of silane coupling agent, 2-6 parts of sulfur, 2-13 parts of accelerator and 0.1-1 part of scorch retarder, and uses three types of rubber, natural rubber, styrene-butadiene rubber and solution-polymerized styrene-butadiene rubber, uses the synergistic effect of accelerator, sulfur and zinc oxide as the vulcanization system to fully vulcanize the rubber, uses carbon black for reinforcement, and uses tackifying resin to increase the adhesion between rubber and skeleton The bonding of materials is carried out in combination with stearic acid, polyethylene glycol, dispersant, antioxidant, protective wax, silane coupling agent, anti-scorch agent and the like. By adjusting the formula and adding a heat stabilizer, the dynamic performance of rubber products at high temperatures is improved and the heat generation of rubber vulcanized rubber is reduced. After a large number of repeated experiments, the optimal dosage of the heat stabilizer and other components is determined to obtain the above-mentioned formula. The spigot glue formula for preventing spigot hollowing of the present invention can effectively improve the formula rigidity, tensile strength, tear strength, small permanent deformation, good flexure and resilience, can improve the bonding force of various components, enhance the bonding strength with the surface of contacting components, has low heat generation and good heat aging resistance, and the cohesive force is greater than the destructive force generated by the outside world or high-speed movement, which can greatly reduce spigot hollowing, reduce a series of early damage quality problems such as spigot cracking and spigot explosion, and reduce the huge threat to vehicle driving safety.

[0031] The present application discloses a method for preparing a low-heat-generating tire bead rubber for preventing bead hollowing. The method has the advantages of simple processing and low cost. The method upgrades the performance of the existing tire bead rubber for preventing bead hollowing and solves the technical problem that the existing tire bead rubber is prone to bead hollowing. The purpose of improving the tire bead hollowing is to reduce the risk of the tire bead hollowing, improve the safety performance of the tire, and meet the product needs of customers.

[0032] The present invention also discloses the application of the above-mentioned anti-valve rubber in the preparation of valve tires. The tires made with the valve rubber can significantly reduce valve voids. Compared with the previous valve rubber, the valve voids can be reduced by about 90%, and the performance of tire durability tests can be improved. The valve performance is excellent and can meet the customer's tire performance requirements. DETAILED DESCRIPTION

[0033] The specific technical scheme of the present invention is described below in conjunction with specific examples 1-6 and comparative examples 1-6:

[0034] Example 1

[0035] A spout glue for preventing the spout from being empty, the formula of which is as follows by weight:

[0036] Natural rubber (SMR20# from Gemas Co., Ltd.) 30 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 35 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 35 parts, zinc oxide 1.0 parts, stearic acid 2.0 parts, polyethylene glycol-PEG4000 1.0 parts, dispersant 1.5 parts, antioxidant (4020) 1.5 parts, protective wax 1.5 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 3.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 1.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 15 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 45 parts, white carbon black 30 parts, silane coupling agent 3.0 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 2.0 parts, accelerator NS 1.0 parts, accelerator DPG 0.5 parts, accelerator DTDM 0.5 parts, scorch retarder CTP 0.1 parts.

[0037] The above-mentioned anti-sub-mouth empty sub-mouth glue can be prepared by the following method:

[0038] (1) Mixing:

[0039] First, the raw materials are transported into the factory for inspection, and the glue is dried and cut as needed, or the raw materials are directly added and automatically weighed according to the formula given above;

[0040] Then transfer the weighed raw materials into the internal mixer and mix them under a pressure of 50N / cm 2 , automatically mix for 180 seconds at a temperature of 150°C and a speed of 25-45rmp, and then discharge the glue.

[0041] (2) Extrusion tableting:

[0042] After the debinding, the tablets are extruded by twin screws, passed through a spacer liquid (mainly comprising stearic acid soap and talcum powder), cooled, and stacked to obtain the product.

[0043] Example 2

[0044] A nozzle glue for preventing nozzles from being hollow, the formula of which is as follows by weight:

[0045] Natural rubber (SMR20# from Gemas Co., Ltd.) 40 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 30 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 30 parts, zinc oxide 1.5 parts, stearic acid 1.0 parts, polyethylene glycol-PEG4000 1.5 parts, dispersant 1.5 parts, antioxidant (4020) 2.5 parts, protective wax 2.0 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 4.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 2.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 35 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 25 parts, white carbon black 20 parts, silane coupling agent 2.0 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 3.0 parts, accelerator NS 1.5 parts, accelerator DPG 0.8 parts, accelerator DTDM 0.9 parts, scorch retarder CTP 0.2 parts.

[0046] The above-mentioned anti-sub-mouth hollow sub-mouth glue is prepared by the following method: prepared according to the method of Example 1.

[0047] Example 3

[0048] A nozzle glue for preventing nozzles from being hollow, the formula of which is as follows by weight:

[0049] Natural rubber (SMR20# from Gemas Co., Ltd.) 50 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 25 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 25 parts, zinc oxide 2.0 parts, stearic acid 1.5 parts, polyethylene glycol-PEG4000 2.0 parts, dispersant 2.0 parts, antioxidant (4020) 3.5 parts, protective wax 1.5 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 5.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 4.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 35 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 10 parts, white carbon black 45 parts, silane coupling agent 4.5 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 4.0 parts, accelerator NS 2.5 parts, accelerator DPG 0.9 parts, accelerator DTDM 1.5 parts, scorch retarder CTP 0.3 parts.

[0050] The above-mentioned anti-sub-mouth hollow sub-mouth glue is prepared by the following method: prepared according to the method of Example 1.

[0051] Example 4

[0052] A nozzle glue for preventing nozzles from being hollow, the formula of which is as follows by weight:

[0053] Natural rubber (SMR20# from Gemas Co., Ltd.) 55 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 15 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 30 parts, zinc oxide 2.5 parts, stearic acid 2.5 parts, polyethylene glycol-PEG4000 2.5 parts, dispersant 2.5 parts, antioxidant (4020) 4.5 parts, protective wax 2.5 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 6.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 5.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 15 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 25 parts, white carbon black 50 parts, silane coupling agent 5.0 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 5.0 parts, accelerator NS 3.0 parts, accelerator DPG 1.0 parts, accelerator DTDM 2.5 parts, scorch retarder CTP 0.4 parts.

[0054] The above-mentioned anti-sub-mouth hollow sub-mouth glue is prepared by the following method: prepared according to the method of Example 1.

[0055] Example 5

[0056] A nozzle glue for preventing nozzles from being hollow, the formula of which is as follows by weight:

[0057] Natural rubber (SMR20# from Gemas Co., Ltd.) 60 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 20 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 20 parts, zinc oxide 3.0 parts, stearic acid 3.0 parts, polyethylene glycol-PEG4000 3.0 parts, dispersant 2.0 parts, antioxidant (4020) 5.0 parts, protective wax 2.0 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 7.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 6.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 45 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 35 parts, white carbon black 10 parts, silane coupling agent 1.0 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 5.5 parts, accelerator NS 2.0 parts, accelerator DPG 1.5 parts, accelerator DTDM 2.0 parts, anti-scorch agent CTP 0.5 parts.

[0058] The above-mentioned anti-sub-mouth hollow sub-mouth glue is prepared by the following method: prepared according to the method of Example 1.

[0059] Example 6

[0060] A nozzle glue for preventing nozzles from being hollow, the formula of which is as follows by weight:

[0061] Natural rubber (SMR20# from Gemas Co., Ltd.) 70 parts, styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.) 15 parts, solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.) 15 parts, zinc oxide 2.5 parts, stearic acid 2.0 parts, polyethylene glycol-PEG4000 2.0 parts, dispersant 1.5 parts, antioxidant (4020) 5.5 parts, protective wax 1.5 parts, tackifying resin (styrene-maleic anhydride copolymer resin SMA 3000P) 8.0 parts, heat stabilizer (heat stabilizer TCA-90 of Huangyan Donghai Chemical Co., Ltd.) 6.0 parts, N326 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 35 parts, N330 carbon black (Shanxi Yongdong Chemical Co., Ltd.) 45 parts, white carbon black 20 parts, silane coupling agent 2.0 parts, highly dispersible insoluble sulfur (sulfur content ≥ 95%) 6.0 parts, accelerator NS 2.0 parts, accelerator DPG 1.2 parts, accelerator DTDM 1.8 parts, scorch retarder CTP 0.3 parts.

[0062] The above-mentioned anti-sub-mouth hollow sub-mouth glue is prepared by the following method: prepared according to the method of Example 1.

[0063] Comparative Example 1

[0064] A kind of glue, calculated by weight ratio, its formula is as follows:

[0065] 40 parts of EPDM rubber, 30 parts of natural rubber, 30 parts of solution polymerized styrene-butadiene rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 1.5 parts of life extender A, 2.5 parts of antioxidant, 2.0 parts of protective wax, 2.0 parts of tackifying resin, 2.5 parts of hardening resin, 40 parts of N339 carbon black, 45 parts of N220 carbon black, 10 parts of white carbon black, 1 part of silane coupling agent, 2 parts of highly dispersible insoluble sulfur (sulfur content ≥ 95%), 1 part of accelerator CBS, 1.5 parts of accelerator DPG, and 3.2 parts of accelerator MBTS.

[0066] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0067] Comparative Example 2

[0068] A kind of glue, calculated by weight ratio, its formula is as follows:

[0069] 45 parts of natural rubber, 35 parts of butadiene rubber, 30 parts of styrene-butadiene rubber, 20 parts of EPDM rubber, 8 parts of zinc carbonate, 15 parts of ultrafine calcium carbonate, 2.5 parts of stearic acid, 10 parts of mica powder, 15 parts of white carbon black, 50 parts of high wear-resistant furnace black, 12 parts of high-grade clay, 5 parts of zinc oxide, 2.8 parts of life extender A, 3.5 parts of Total oil, 4 parts of accelerator, 2.5 parts of paraffin mixture, 3.5 parts of RA white powder, 3 parts of insoluble sulfur, 15 parts of carbon black, 3 parts of aluminum hydroxide, 2 parts of magnesium oxide, and 2 parts of silane coupling agent.

[0070] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0071] Comparative Example 3

[0072] A kind of glue, calculated by weight ratio, its formula is as follows:

[0073] 45 parts of natural rubber, 60 parts of butadiene rubber, 30 parts of styrene-butadiene rubber, 25 parts of EPDM rubber, 25 parts of polybutadiene rubber, 8 parts of zinc carbonate, 12 parts of ultrafine calcium carbonate, 3 parts of stearic acid, 5 parts of talc, 35 parts of white carbon black, 50 parts of low-structure high-wear-resistant furnace black, 35 parts of high-grade clay, 7 parts of 6700 resin, 6 parts of zinc oxide, 3 parts of stearic acid, 3 parts of magnesium oxide, 3.5 parts of RE brown crystals, 2 parts of Total oil, 1 part of accelerator, 3.5 parts of paraffin mixture, 3.5 parts of RA white powder, 5.3 parts of insoluble sulfur, 25 parts of carbon black, 2 parts of aluminum hydroxide, 3.5 parts of alkylphenol disulfide, and 3.5 parts of silane coupling agent.

[0074] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0075] Comparative Example 4

[0076] A kind of glue, calculated by weight ratio, its formula is as follows:

[0077] 40 parts of natural rubber, 40 parts of butadiene rubber, 20 parts of reclaimed rubber, 58 parts of carbon black, 10 parts of high aromatic oil, 4 parts of 203 resin, 2.5 parts of stearic acid, 3.5 parts of zinc oxide, 3.5 parts of antioxidant 4020, 1.5 parts of antioxidant TMQ, 2 parts of antioxidant 2241, 1.5 parts of microcrystalline wax 2122, 1 part of special sulfur, 0.4 parts of accelerator DPG, 0.3 parts of accelerator NS, and 0.15 parts of accelerator CBS.

[0078] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0079] Comparative Example 5

[0080] A kind of glue, calculated by weight ratio, its formula is as follows:

[0081] 40 parts of natural rubber (SMR20# from Gemas Co., Ltd.), 30 parts of styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.), 30 parts of solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.), 1.5 parts of zinc oxide, 1.0 parts of stearic acid, 1.5 parts of polyethylene glycol-PEG4000, 1.5 parts of dispersant, 2.5 parts of antioxidant (4020), 2.0 parts of protective wax, 4.0 parts of cashew nut oil-modified phenolic resin, 35 parts of N326 carbon black (from Shanxi Yongdong Chemical Co., Ltd.), 25 parts of N330 carbon black (from Shanxi Yongdong Chemical Co., Ltd.), 20 parts of white carbon black, 2.0 parts of silane coupling agent, 3.0 parts of highly dispersible insoluble sulfur (sulfur content ≥ 95%), 1.5 parts of accelerator NS, 0.8 parts of accelerator DPG, 0.9 parts of accelerator DTDM, and anti-scorch agent CTP 0.2 portion.

[0082] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0083] Comparative Example 6

[0084] 30 parts of natural rubber (SMR20# from Gemashi Co., Ltd.), 35 parts of styrene-butadiene rubber (SBR1502 from Fujian Fuxiang Chemical Co., Ltd.), 35 parts of solution-polymerized styrene-butadiene rubber (SSBR2466 from Taiwan Rubber Co., Ltd.), 1.0 parts of zinc oxide, 2.0 parts of stearic acid, 1.0 parts of polyethylene glycol-PEG4000, 1.5 parts of dispersant, 1.5 parts of antioxidant (4020), 1.5 parts of protective wax, 3.0 parts of 6700 resin, 15 parts of N326 carbon black (from Shanxi Yongdong Chemical Co., Ltd.), 45 parts of N330 carbon black (from Shanxi Yongdong Chemical Co., Ltd.), 30 parts of white carbon black, 3.0 parts of silane coupling agent, 2.0 parts of highly dispersible insoluble sulfur (sulfur content ≥95%), 1.0 parts of accelerator NS, 0.5 parts of accelerator DPG, 0.5 parts of accelerator DTDM, and 0.1 parts of anti-scorch agent CTP.

[0085] The above-mentioned sub-mouth glue is prepared by the following method: prepared by referring to the method of Example 1.

[0086] Table 1: Weight ratio of components in Examples 1 to 6

[0087]

[0088] The performance of the sub-mouth glue prepared in the above examples and comparative examples was tested, and the test items and test results are shown in Table 2-5.

[0089] Table 2 Performance test results of the rubber compound prepared by the sub-mouth glue of the embodiment

[0090]

[0091]

[0092] Table 3 Comparative Example of the performance test results of the rubber compound prepared by the sub-mouth rubber

[0093]

[0094]

[0095] The results of indoor durability test of finished tires prepared by the rubber of Table 4 Example are as follows:

[0096]

[0097] The results of indoor durability test of finished tires prepared with the rubber of Table 5 Comparative Example are as follows:

[0098]

[0099] From the test results in the above table, we can see that:

[0100] When the total number of carbon black used in Examples 1 and 3 is the same (both are 90 parts) and the number of heat stabilizers is different, the finished tires prepared from the obtained rubbers have good tensile strength (27.22 and 29.03, respectively), rebound value (61 and 63, respectively), R97 anti-sulfurization inversion time (46.89 and 48.42, respectively) and compression fatigue test temperature rise (18.2 and 15.9, respectively), and other physical properties do not change much, indicating that when the amount of carbon black used is the same, the more the number of heat stabilizers used, the greater the tensile strength and rebound value of the rubber compound, the longer the anti-sulfurization inversion time, the lower the compression heat generation, the better the heat resistance and durability test performance of the obtained rubber compound, and the better the comprehensive physical properties.

[0101] When the total amount of carbon black used in Examples 5 and 6 is different (90 parts and 100 parts, respectively), and the amount of heat stabilizer is the same, the finished tire prepared by the rubber obtained in Example 6 has a tensile strength (29.88, 31.02, respectively), a rebound value (62, 65, respectively), an R97 anti-sulfurization inversion time (49.21, 49.87, respectively) and a compression fatigue test temperature rise (15.1, 14.3, respectively) that is significantly better than that of Example 5. This indicates that when the amount of carbon black is reduced, the finished tire prepared by the rubber obtained will have better comprehensive physical properties, and the R97 anti-sulfurization inversion time and compression fatigue test temperature rise will be better.

[0102] The finished wheels prepared with the rubber obtained in Examples 1, 2, 3, 4, 5 and 6, especially the finished tires prepared with the rubber obtained in Examples 4, 5 and 6, have R97 anti-sulfurization reversion time significantly longer than the R97 anti-sulfurization reversion time of the finished tires prepared with the rubber obtained in the comparative example, which are 46.89, 47.15, 48.42, 48.8, 49.21 and 49.87 respectively; at the same time, the temperature rise of the compression fatigue test is significantly lower than the temperature rise of the compression fatigue test of the finished tires prepared with the rubber obtained in the comparative example, which are 18.2, 17.3, 15.9, 15.3, 15.1 and 14.3 respectively. Therefore, the tires prepared with the rubber of the present invention have higher anti-sulfurization reversion, tensile strength and rebound value, low compression heat generation, and improved heat resistance and durability of the finished tires. It can significantly reduce the gap between the nozzles, reduce a series of early quality problems such as nozzle cracking and nozzle explosion, and reduce the huge threat to vehicle driving safety.

[0103] Comparative Examples 1, 2, 3, and 4 are finished wheels prepared with existing tire tip rubber formulas. Their tensile strength (respectively 25.78, 25.36, 26.01, and 25.12), rebound value (respectively 45, 46, 43, and 44), R97 anti-vulcanization recovery time (respectively 30.12, 29.15, 29.78, and 30.14) and compression fatigue test temperature rise (respectively 25.14, 25.89, 26.75, and 26.37) are all average, and the heat resistance and durability test performance of the obtained tip rubber are poor.

[0104] Comparative Examples 5 and 6 do not add heat stabilizers, and comparative document 5 uses cashew nut oil modified phenolic resin and comparative document 6 uses 6700 resin. It can be seen from the test results that the finished tires prepared without using heat stabilizer TCA-90 and styrene-maleic anhydride copolymer resin have tensile strength (26.66 and 26.54, respectively), rebound value (52 and 53, respectively), R97 anti-sulfurization inversion time (32.87 and 30.78, respectively) and compression fatigue test temperature rise (26.79 and 26.98, respectively) are significantly worse than those of Examples 1-6 of the present application. The tensile strength and rebound value of the sub-mouth rubber are the lowest, the anti-sulfurization inversion time is at the end, the compression heat generation is high, the heat resistance and durability test performance of the obtained sub-mouth rubber are average, and the sub-mouth cavity cracking is serious in the durability test.

[0105] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a low heat generation tire tip rubber for preventing tip cavities, characterized in that: The tire rubber is composed of the following components in parts by weight: 30-70 parts of natural rubber, 15-35 parts of styrene-butadiene rubber SBR1502, 15-35 parts of solution-polymerized styrene-butadiene rubber SSBR2466, 1.0-3.0 parts of zinc oxide, 1-3 parts of stearic acid, 1-3 parts of polyethylene glycol, 1.5-2.5 parts of dispersant, 1.5-5.5 parts of antioxidant, 1.5-2.5 parts of protective wax, 3-8 parts of tackifying resin, 1-6 parts of heat stabilizer, 45-100 parts of carbon black, 3-5 parts of silane coupling agent, 2-6 parts of sulfur, 2-10 parts of accelerator, and 0.1-0.5 parts of scorch retarder; The styrene-butadiene rubber is styrene-butadiene rubber SBR1502, which is a low-temperature emulsion styrene-butadiene rubber, with volatile matter ≤0.75%, total ash ≤0.75%, organic acid 5.62%, soap ≤0.50%, combined styrene 23.5%, tensile strength ≥23.7Mpa, and elongation ≥415%; The solution polymerized styrene butadiene rubber is solution polymerized styrene butadiene rubber SSBR2466, with a Mooney viscosity ML1+4 at 100°C of 70-80 and a styrene content of 20-22%; The thermal stabilizer is thermal stabilizer TCA-90, with a melting point of ≥78.0°C, ash content ≤28.0%, and heating loss ≤4.0%; The tackifying resin is a styrene-maleic anhydride copolymer resin, which is a product of Crayville Company with a model number of SMA 3000P; The natural rubber is natural rubber SMR20#; The carbon black is composed of three carbon blacks in the following weight ratios: 15-45 parts of N326 carbon black, 10-45 parts of N330 carbon black and 10-50 parts of white carbon black; The method for preparing the low heat generation tire tip rubber for preventing tip from being empty comprises the following steps: (1) Mixing: Weigh the above raw materials according to the weight ratio, transfer the weighed raw materials into the internal mixer, and mix them under a pressure of 45-55N / cm 2 , automatically mix for 180 seconds at a temperature of 145-155°C and a rotation speed of 25-45 rpm, and then discharge the glue; (2) Extrusion tableting: After debinding, the product is extruded and tableted by twin screw extruder. After passing through the isolation liquid, it is cooled and stacked to obtain the product.

2. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The accelerator is composed of three accelerators in the following weight ratio: 0.5-3 parts of accelerator NS, 0.5-1.5 parts of accelerator DPG and 0.5-2.5 parts of accelerator DTDM.

3. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The antioxidant is selected from at least one of N-phenyl-α-aniline, N-phenyl-N'-isopropyl-p-phenylenediamine, N-N'-diphenyl-p-phenylenediamine and antioxidant 4020.

4. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The dispersant is KO-311.

5. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The silane coupling agent is coupling agent HP-669.

6. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The sulfur is selected from granular sulfur with a sulfur content of ≥95%, and is highly dispersed insoluble sulfur.

7. The method for preparing a low heat build-up tire bead rubber for preventing bead hollowing according to claim 1, characterized in that: The density of the tire rubber is 1.166-1.169kg / dm 3 .

8. Use of the low heat build-up tire bead rubber for preventing bead hollowing prepared by the method according to any one of claims 1 to 7 in tires.

Citation Information

Patent Citations

  • Tire bead steel wire rubber and preparation method thereof

    CN111607133A

  • Rubber composition and pneumatic tire

    JP2000290433A